2015
DOI: 10.1111/ajfs.12086
|View full text |Cite
|
Sign up to set email alerts
|

Size, Value, and Momentum in Emerging Market Stock Returns: Integrated or Segmented Pricing?

Abstract: In this paper, we examine size, value, and momentum patterns in the stock returns of four emerging market regions—Latin America, EMEA, Asia, and BRIC. We document a strong and highly significant value effect, and a strong but less significant momentum effect. Substantial value and momentum premiums are also present for big stocks and the overall premiums are not mainly driven by small stocks. Furthermore, the value patterns in emerging markets are more pronounced than in developed markets. In order to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 25 publications
7
23
0
Order By: Relevance
“…When it comes to international markets, or emerging markets, findings, however, are not always in agreement. Besides supportive evidences found in research studies, such as Fama and French () for value effect in international markets, Wong () for size effect in a single emerging market like Singapore, Groot, Pang, and Swinkels () for value and size effect in a sample of twenty four most liquid frontier emerging markets, Hanauer and Linhart () for strong and highly significant value effect in four emerging market regions—Latin America, EMEA, Asia, and BRIC, or Ho and Chang () for liquidity effect in Chinese market etc., we also see evidences of the non‐existence of these effects in other research studies and other markets.…”
Section: Introductionmentioning
confidence: 65%
“…When it comes to international markets, or emerging markets, findings, however, are not always in agreement. Besides supportive evidences found in research studies, such as Fama and French () for value effect in international markets, Wong () for size effect in a single emerging market like Singapore, Groot, Pang, and Swinkels () for value and size effect in a sample of twenty four most liquid frontier emerging markets, Hanauer and Linhart () for strong and highly significant value effect in four emerging market regions—Latin America, EMEA, Asia, and BRIC, or Ho and Chang () for liquidity effect in Chinese market etc., we also see evidences of the non‐existence of these effects in other research studies and other markets.…”
Section: Introductionmentioning
confidence: 65%
“…Later on, Barry et al (2002), Kargin (2002), Rouwenhorst and Salomons (2003) have demonstrated benefits of stock selection based on value-related variables measures, like price-to-book ratio, price-to-earnings ratio or price-to-cash flow ratio for EEM investors. Also, the most recent studies confirm that the value premium is present in emerging markets, although it may vary from country to country (e.g., Dimson et al, 2014;Cakici et al, 2013;Lischewski and Voronkova, 2010;Hanauer and Linhart, 2015;Zaremba, 2015). Most recently, Zaremba and Czapkiewicz (2016) identified and replicated ten various value-oriented return-predictive signals in a very similar sample covering the Czech Republic, Hungary, Poland, Russia, and Turkey.…”
Section: Related Literaturementioning
confidence: 92%
“…This may, in turn, additionally contribute to portfolio turnover and negatively impact the profitability of the portfolio. Finally, the fundamentally indexed portfolios are tilted towards value style, which proved very profitable in Emerging Europe (Cakici et al, 2013;Hanauer and Linhart, 2015;Zaremba, 2015). The exposure to the value factor may potentially result in an improved performance of the fundamentally weighted indexes and portfolios.…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed the existence of the value and momentum effects in all the 18 emerging markets, but not for Eastern Europe (no momentum). Hanauer and Linhart (2015) also used the Carhart model to examine four emerging market regions: Latin America, EMEA (Europe, the Middle East and Africa), BRIC (Brazil, Russia, India, and China) and Asia. They detected a strong evidence noting the effect of the value factor, but they had weak evidence noting the effect of the momentum factor in those regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emerging markets have not been studied at the same level in detail despite the fact that emerging stock markets have an important role to play within the world portfolio. The importance of such emerging economies, and stock markets are constantly increasing (Hanauer & Linhart, 2015), hence such markets should not exist in obscurity.…”
Section: Introductionmentioning
confidence: 99%